Estetika Tari Piriang Hoyak Badarai Sanggar Sarai Sarumpun Di Kota Padang - Cesi Frinamala Nazar; Darmawati Darmawati (Universitas Katolik Widya Karya Malang, 2023)
The research aims to reveal and describe the Aesthetics of Hoyak Badarai Plate Dance Sarai Sarumpun Studio in Padang City. This type of research is qualitative research with descriptive methods of analysis. This research instrument is the researcher himself and is assisted by supporting instruments such as stationery and cameras. Data collection techniques are carried out by means of literature studies, observations, interviews and documentation. The steps of analyzing data are data collection, data reduction, data model and drawing conclusions. The results showed that the aesthetics of Piriang hoyak badarai Dance 6 principles, namely the principle of organic unity. Theme Principle, Theme Variation Principle, Balance principle, Development principle and Level Layout principle which are also associated with elements in dance, where dance elements are also divided into 2, namely the main elements such as movement and supporting elements in dance such as floor patterns, dancers, dance accompaniment music, makeup and clothing, property and performance venues. Appearance is one of the fundamental parts that all art objects or art events have. For art performance, there are three elements that play a role, namely talent, skills, and facilities or media. This element was used to study it as the Aesthetics of Piriang Hoyak Badarai Dance at Sarai Sarumpun Studio in Padang City. Piriang Hoyak Badarai dance is a dance that illustrates the nature of community cooperation in working on rice fields starting from hoeing until rice returns to the granary. This is the background behind the creation of Hoyak Badarai Dance. And the source of the gerkana itself is taken from the Minangkabau Basic Motion.